Simulation using default model in ATHENA/SSUPREM4 - Sharifah Norfaezah, Sabki; M. D. R., Hashim (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.